OBJEKTIVITAS PEMBERITAAN PEMILU PRESIDEN 2019 DI DETIKCOM - Dewi Gili Amritha, Dewa Ayu Agung; Pradipta, Ade Devia; Amanda Gelgel, Ni Made Ras (E-Jurnal Medium; Vol 1 No 2 (2021): Jurnal Ilmu Komunikasi 2021, 2021)
Objectivity at news has become significant point in Presidential Election 2019. The voters should be smart at choosing one of the candidates due to the influence of media which provide news about the election.1Detikcom became the fifth most popular media in Indonesia according to ranking site, Alexa.com. Quantitative content analysis with descriptive approach was conducted within this study in order to recognize the objectivity of media while posting the news. In addition, it was conducted by analysing news about Presidential Election 2019 in1Detikcom. Thestheory applied within this study was the theory of objectivity by1Westersthal which consists of four indicators (truth, relevance, balance, and neutral presentation), and twelve samples of news were examined. The result shows that the news about Presidential Election 2019 on the news portal of Detikcom meets the four indicators of news objectivity, factuality (factual, accurate, complete, and relevant) and impartiality (non-evaluative and non-sensational). Keywordi: Content analysis,1Detikcom, News of Presidential Election 2019, Objectivity